Study to determine the chemical constituents, antibacterial ability, and antioxidant activity of the red pepper (Piper Nigrum l.) essential oil in Gia Lai Province, Vietnam - Van LOI, Nguyen; Thi BINH, Pham; Thi THANH, Khong; NGOC, Nguyen Thi Thanh (Food Science and Technology, 2023)
Pepper often contains aromatic components, spicy ingredients, and biologically active ingredients. The common chemical components in pepper are essential oils and alkaloids. Essential oils are abundant in pepper, usually accounting for about 1.5–2.2%. Therefore, this study aimed to primarily analyze the constituents, antioxidant activity, and inhibition test microorganisms which are very essential. By using the gas chromatography-mass spectrometry method, 17 components in red pepper essential oil have been identified, of which nine constituents are hydrocarbons (such as 41.35% monoterpenes and 3.55% sesquiterpenes) and the rest are oxygenated hydrocarbons (36.62% alcohols and 17.75% aldehydes). The red pepper essential oil has strong antibacterial ability against experimental strains of microorganisms such as Bacillus cereus, Staphylococcus aureus, Listeria monocytogenes, Streptococcus viridians, Escherichia coli, Proteus vulgaris, Salmonella enteritidis, and Aspergillus flavus with an average antibacterial circle diameter of 15.29 mm. Besides, it has also been determined that the antioxidant activity of red pepper essential oils was 37.69±0.12%.